أبجديات النظرية الشعرية في كتابات نزار قباني - زودة, فطيمة (جامعة الوادي - university of Eloued, 2021)
الشعر فضاء رحب يحتضن كل المفارقات ويجمع كل الأضداد،لأنه ضرب من الخيال المرتبط بأعماق الذات وقضايا الواقع.والقصيدة تولد حقيقة ثم تنمو وتتطور وفق مراحل معينة،وما سمي الشعر شعرا و قصيدا إلا لأن قائله قصد إليه قصدا،فنظم الشعر هو تلبية لمتطلبات ومعايير استقرت في وعي المتلقي،وصارت مهمة فنية ينجزها الشاعر ويكتبها، مما يوسع دائرة القصد ويحقق جمالية الأثر. ولعل هذه الفجوة التي لم تستطع محاولات النقاد ملأها، هي ما جعلت الشعراء يحددون بعض الأمور المتعلقة بفنهم الشعري؛ لذا ركزنا في تحديد أسس النظرية الشعرية من خلال رؤية أصحابها لها،فهم أدرى بما يعتريهم لحظة الكتابة، كما أن تجربتهم الشعرية كفيلة بوضع إجابات تساءل عنها النقاد طيلة عصور خلت، ومن الشعراء النقاد الذين انفردت بهم هذه الدراسة الشاعر " نزار قباني " من خلال كتابيه: ماهو الشعر؟ وقصتي مع الشعر، اللذين وقف فيهما الشاعر على كثير من المفاهيم الخاصة بفن الشعر، كما يعد تجربة نقدية أعادت تشكيل مفهوم الشعر وفق تمازج فني بين "نزار" الشاعرو" نزار" الناقد. Poetry is a vast space that embraces all the paradoxes and oppositions, for it is a form of imagination related to the depths of the self and issues of reality. The poem generates a reality and then grows and develops through certain specific stages. Poetry is called “poetry” and “qasid” (derives from the verb ‘qasada’ (to intend) in Arabic) except because those who said it intended it on purpose. Poetry, thus, meets the requirements and standards settled in the consciousness of the reader, which has become an artistic task that the poet accomplishes and writes. This, then, led to expanding the circle of intention and achieving the aesthetic impact. This gap, which has not been addressed by critics, is perhaps what made the poets determine some basic matters related to their poetic art. Therefore, we focused on identifying the foundations of the poetic theory from the standpoint of the writers. The latter are more aware of what is going on while writing their poems. Furthermore, their poetic experiences would enable them provide answers to certain questions raised by critics for centuries. This study focused on one of the distinguished critical poet, NizarQabbani, and examines his two well-known books, namely “What is poetry?” and “My story with poetry”. In these two books, the poet examined many concepts related to the art of poetry. They are also considered a critical experiment that reconceptualized the notion of poetry according to an artistic intermingling between "Nizar" the poet and "Nizar" the critic.
مقال
Keywords: الشعر ؛النظرية الشعرية؛ نزار قباني؛ النقد؛ التجربة الشعرية; poetic theory; Nizar Qabbani; criticism ; poetic experience